Technology in the development of numerical thinking - Quiñones Caicedo, Segunda Gloria (Omnia, 2024)
This article presents fundamental notions about the teaching-learning process in the area of mathematics from the use of technology and the development of numerical thinking for problem solving supported by UNESCO positions, curricular guidelines of the Colombian Ministry of Education, Ibarra, among others. The research is methodologically, positivist-quantitative of a descriptive type and non-experimental - transectional field design. The sample was established with the entire population of 15 teachers and 85 ninth grade students of the Educational Institutions of Huila in Colombia. The technique to collect the data was the survey and as an instrument the structured questionnaire with response categories Always, Sometimes, Never. Likewise, an interview was carried out with 5 teachers of the coordination of mathematics for the technological processes that have allowed the development of some premises in the final considerations